ADAPTASI SEBAGAI STRATEGI BERTAHAN HIDUP MANUSIA - Amir Mahmud (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2016)
Humans can survive on the results of utilizing the naturalresources around him. Animals, plants, air, water, minerals,everything in the universe is taken advantage to meet the needsof human life. Disaster after the cause of global warming. Nitrousoxide is produced by vehicle and industrial emissions, whilemethane emissions are caused by industrial and agriculturalactivities. The environmental damage caused by humanintervention in order to take advantage of nature to make endsmeet. But in exploiting the human nature often do not payattention to the balance of natural ecosystems so that the originalharmony be shaken. It is characterized by the loss of one or moreconsumers in certain trophic levels resulting population of certainspecies becomes abundant and others missing. Besides theenvironmental damage in this case the forest is potentiallycreating global warming caused by greenhouse gases in the formof carbon dioxide gas (CO2) resulting from the burning of fossilfuels and the use of CFCs. It is necessary for adaptation to thenew environment in order to survive. So maybe somedayhumans and other organisms evolve to adapt or adjust to a newenvironment where he lives. To prevent damage to the earthnecessary preventive measures friendly to the environment.